Nature and the Constitution: Indigenous Perspectives and Proposals for the Crisis - Galdámez Zelada, Liliana; Millaleo Hernández, Salvador (Acta Bioethica, 2020)
This paper assesses how the law and the 1980 Constitution deal with nature. This view contrasts with the perspective of the philosophies of the indigenous Andean and Mapuche peoples which consider the interrelation, interdependence and reciprocity in the relationships between society and nature. From the standpoint of the environmental problems that science has systematized and that affect the world and the country, this paper puts forward proposals for a new configuration for issues concerning the environment and nature in the Constitution.